Gambaran Mengenai Metode Mengajar Sesuai dan Tidak Sesuai Dikembangkan dalam Program TK - Yenny Yenny (PG-PAUD Trunojoyo, 2017)
With the increasing understanding of how young children develop and learn, there has been a greater emphasis on the education of young children. This study aims to obtain a description of appropriate and inappropriate teaching methods developed in a kindergarten program, specifically in the village of South Meruya. This research is qualitative descriptive, using interview method to teaching method of kindergarten teacher. The subjects consisted of 8 kindergarten teachers, consisting of 4 teachers of kindergarten and 4 teachers of kindergarten. The results obtained from this research are the kindergarten teachers in Meruya Selatan Village have shown appropriate teaching methods developed in the kindergarten program almost on all components except the teaching strategy component (addressing the ideas conveyed by the children), content and curriculum approach (aesthetic expression), reciprocal relationship with parents, and program policies (teacher-child ratio).